FISH HANDLING PROCESS LANDED AT BRONDONG FISHING PORT, LAMONGAN - Saraswati, Exist; Ningtyas, Rosidah Wahyu; Noor, M. Tajuddin; Yusrudin (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
PPN Brondong is one of the largest fishing ports in East Java. This port provides various facilities to support fisheries activities, including a Fish Auction Place (TPI), which has now changed its name to the Fish Marketing and Distribution Center (PPDI). All fish handling activities, from loading and unloading to distribution, take place at this location. Handling of fishery products is a crucial process that can determine the quality and selling price of fish. This study was conducted to identify and analyze the catch handling process carried out at PPN Brondong. The study was conducted in June 2025. The method used was a survey with interviews and direct observation in the field. The collected data was then analyzed descriptively qualitatively. Based on the research results, fish handling at PPN Brondong consists of fresh whole fish raw materials stored in the ship's hold, sorting, washing, weighing, and distribution. Distribution can be done directly to the market or stored first in cold storage. Handling of the catch at PPN Brondong has been carried out quite well, demonstrated by rapid handling to maintain the freshness and quality of the fish. However, there are still some handling procedures that need to be improved in terms of cleanliness so as not to contaminate the fish caught. Key words: catch, fish handling, fish quality